Design of dual winding permanent magnet synchronous machines for hybrid electric vehicle accessory drives - Mese, Erkan; Ayaz, Murat; Tezcan, Murat; Yilmaz, Kadir (INDERSCIENCE ENTERPRISES LTD, 2015)
This paper presents a new accessory drive system for hybrid electric vehicles (HEVs). This new concept involves a dual winding electric machine with simultaneous motor and generator functions. The electric machine provides power for all accessory loads such as the steering pump, compressors and 12 V loads. When the engine is off, the electric machine starts its motoring action and provides mechanical power to the accessory loads. Simultaneously, the generator windings provide power for the 12 V loads. The proposed structure could be a viable choice for fault-tolerant applications because of the concentrated winding type that maintains electrical and magnetic isolation. Design considerations of the proposed electric machine are outlined in the paper. The distributed winding topology and concentrated winding topologies are also compared. Analytical proof of magnetic decoupling is presented and experimentally verified.
Keywords: electric machine design; PMSM; permanent magnet synchronous machine; concentrated winding; conformal mapping; analytical magnetic decoupling; DWPMSM; dual winding PM synchronous machine; fault-tolerant operation; drive by wire; hybrid electrical vehicle application; COGGING TORQUE; BLDC MOTOR; SLOT; PARAMETERS; Engineering; Transportation